The Implementation of Restorative Justice Approach through Restorative Justice Handling in Criminal Acts of Fraud & Embedding - Risqi Akbar; Sri Kusriyah; Achmad Sulchan (Universitas Islam Sultan Agung, 2022)
The objectives of this study are as follows: To find out and analyze the application of case settlement through a restorative justice approach in handling fraud and embezzlement crimes. The method used by the researcher is juridical sociological approach. The specifications in this study are descriptive. The sources and types of data in this study are secondary data obtained from library studies. Data analyzed qualitatively. Based on the results of the study that the application of case resolution through a restorative justice approach in handling the crime of fraud and embezzlement is carried out through a mechanism of several stages so that the action is truly an effort to enforce the law by prioritizing the principle of restorative justice. The application of this principle is a breakthrough in law enforcement, so that it can speed up the settlement of cases, the costs incurred are relatively cheaper and indirectly have an impact on improving the performance of investigators.